Antimicrobial activity of 50 plant extracts - Zazharskiy, Vladymyr; Zazharskiy, Volodymyr; Zazharskyi, Vladymyr; Zazharskyi, Volodymyr; Zazharskiy, V.; Zazharskyi, V.; Zazharskiy, Volodymyr V.; Zazharskiy, V. V.; Zazharskyi, V. V.; Zazharsky, V. V.; Зажарський, Володимир Володимирович; Davydenko, Pavel; et al. (Oles Honchar Dnipro National University, 2019)
Antibacterial activity of plants is a subject of interest in the search for new antibiotics and fungicidal preparations. This article analyzes the effectiveness of the action of extracts of plants on microorganisms: six species of bacteria (Salmonella typhimurium, Listeria monocytogenes, Escherichia coli, Klebsiella pneumoniae, Corynebacterium xerosis, Proteus vulgaris) and one fungus (Candida albicans). For the assay, we used herbal material of 50 species (seeds, grass, shoots, leaves, compound fruit, peel) obtained at different periods of the growing season. We studied Levisticum officinale, Petroselinum crispum, Nerium oleander, Vinca minor, Eleutherococcus senticosus, E. sieboldianus, Yucca filamentosa, Artemisia annua, Echinacea purpurea, Matricaria recutita, Tanacetum vulgare, Betula pendula, Corylus avellana, Buxus sempervirens, Humulus lupulus, Crassula ovata, Bryophyllum daigremontianum, Juniperus communis, Platycladus orientalis, Cycas revoluta, Calluna vulgaris, Rhododendron ferrugineum, Ceratonia siliqua, Trigonella foenum-graecum, Ribes nigrum, Phellinus tuberculosus, Lavandula angustifolia, Melissa officinalis, Monarda fistulosa, Origanum vulgare, Salvia sclarea, Laurus nobilis, Punica granatum, Hibiscus rosa-sinensis, Menispermum dauricum, Ficus benjamina, Morus alba, Paeonia suffruticosa, Picea abies, Adonis vernalis, Amelanchier ovalis, Prunus armeniaca, Crataegus monogyna, Citrus sinensis, Salix babylonica, Bergenia crassifolia, Schisandra chinensis, Taxus baccata and Xanthoria parietina. The alcohol tincture was filtered with sterile multi-layer gauze disc filters. Before the discs were put on the surface of agar with inoculation of the corresponding culture, they were dried in a sterile laminar box under ultraviolet rays. Antibacterial activity of various tinctures was determined by the disk diffusion method in agar with the measurement of the diameter of the growth suppression zone of the culture using a template ruler. Maximum inhibiting effect was achieved for Punica granatum on K. рneumonia, L. monocytogenes, S. typhimurium, P. vulgaris, C. хerosis and E. сoli, Lavandula angustifolia – on P. vulgaris, K. рneumonia and S. typhimurium, Echinacea purpurea – on C. аlbicans, E. сoli, P. vulgaris, K. рneumonia, Bergenia crassifolia – on P. vulgaris, K. pneumonia and S. typhimurium. Антибактеріальна активність рослин є предметом зацікавленості у пошуку нових антибіотиків та фунгіцидних препаратів. У цій статті проаналізовано ефективність дії екстрактів рослин на мікроорганізми: шість видів бактерій (Salmonella typhimurium, Listeria monocytogenes, Escherichia coli, Klebsiella pneumoniae, Corynebacterium xerosis, Proteus vulgaris) та одного гриба (Candida albicans). Для аналізу ми використовували рослинний матеріал з 50 видів (насіння, трава, пагони, листя, складені плоди, шкірка), отриманий у різні періоди вегетаційного періоду. Максимальний гальмуючий ефект був досягнутий для Punica granatum на K. rneumonia, L. monocytogenes, S. typhimurium, P. vulgaris, C. heerosis та E. сoli, Lavandula angustifolia - на P. vulgaris, K. rneumonia та S. typhimurium, Echinacea purpurea - на C. albicans, E. soli, P. vulgaris, K. rneumonia, Bergenia crassifolia - на P. vulgaris, K. pneumonia та S. typhimurium.
Антимікробна активність 50 рослинних екстрактів
Зажарський Володимир Володимирович https://orcid.org/0000-0003-2674-2494 Давиденко Павло Олександрович https://orcid.org/0000-0002-8425-3835 Кулішенко Олег Миколайович https://orcid.org/0000-0001-6801-2380 Боровик Ірина Володимирівна https://orcid.org/0000-0001-5958-8396
Keywords: Candida albicans; Candida albicans; Salmonella typhimurium; Salmonella typhimurium; Listeria monocytogenes; Listeria monocytogenes; Escherichia coli; Escherichia coli; Klebsiella pneumoniae; Klebsiella pneumoniae; Corynebacterium xerosis; Corynebacterium xerosis; Proteus vulgaris; Proteus vulgaris